Phylogenetic Analysis of P4b Gene of Fowl Pox Virus inNaturally Infected Backyard Chicken - Molika, Kottapu; Samath, Valeti; Chowdary, Chitturi Sudha Rani; Sree, Chittithoti Jyothi; Vishnu, Pothanaboina Guru; Devi, Vemuri Rama (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
In the present study, fowl pox was diagnosed in 129 backyard chicken based on gross and histopathological lesions. Fowl pox was characterised by pock nodular lesions on featherless parts of body(cutaneous form) and purulent, cheesy patches in upper respiratory tract(diphtheritic form). Tissue samples revealed Bollinger bodies in epithelial cells on histopathology. Among these, extraction of DNA was carried out from cutaneous and diptheretic lesions from 29 fowl pox affected chicken. Molecular diagnosis of fowl pox was performed by amplification of P4b gene of fowl pox virus using specific primers  and obtained a desired amplicon of 578bp. Nucleotide sequencing and phylogenetic analysis of four cutaneous fowl pox samples revealed that they were in close relation with the FPV isolates from Singapore, North America and USA (KY464130, MH175285 and KC017961 with an identity of 97.28%, 97.21% and 97.16% respectively) when compared to FPVs isolated from Portugal, Brazil, Jammu and Kashmir and India (KM974727, KX863706, MF496042 and HM481406 respectively with an identity of 96.66% to 96.86%).
Keywords: Bollinger bodies; Fowl pox virus; P4b gene; Phylogenetic analysis